SIKU: Mixing high-tech with ancient know-how - Joel Heath (The UNESCO Courier, 2019)
An Inuktitut word for sea ice, SIKU today refers to a web platform that is revolutionizing access to the ancient knowledge and current research of communities living in Canada's Arctic zone. A story that began modestly with a few snap-shots of eider ducks struggling for survival on the ice floe has evolved into an extraordinary project over fifteen years, combining the oldest knowledge with the most modern technologies.